UNSUR-UNSUR MAGIS DALAM LIRIK LAGU MINANGKABAU - Nindie Cecioria (Jurnal Elektronik WACANA ETNIK, 2011)
Minangkabau people believe in magical practice. This believeness also reflected on their songs. This article describes that matter through song lyrics. Using sociological approach with library research and interview, the result shows that Minangkabaukabau song (Gasiang Tangkurak, Sampelong, Limau Kiriman Urang, and Kasiak Tujuah Muaro) have magical practice contents. Those contents also reflect one of cultural tradition of Minangkabaukabau people.